Answer:
A) 70%
B) 95%
Step-by-step explanation:
A) $200 to $340
Increase = $340 - $200 = $140
Percentage of increase = $140/$200 * 100% = 70%
B) Additional $50
Increase = $140 + $50 = $190
Percentage of increase = $190/$200 * 100% = 95%
Since it decreases by 36 each year, the change would be 36+36+36+36=36*4=144
For a, we can plug in values for t, so 2000-(200*1)=1800 for the first year,
2000-(200*2)=1600 - do you see the pattern here? It subtracts by 200 every year, so 1600-200=1400 for the third year and 1400-200=1200 for the fourth year.
2.43 + 1.62 + 124.77 = 178.82 Because all you have to do is add up all the numbers (Don't take the decimals out, leave them in) And then you get: 178.82.
Hope I helped!
- Amber
Answer:
48
Step-by-step explanation:
![y = 0](https://tex.z-dn.net/?f=y%20%3D%200)
is basically the horizontal axis.
First, find the integral of x^2-25.
Remember that
integral of a constant is that constant times x.
Also that
to take the integral of a power function, add 1 to the degree and divide by that same degree.
![y = {x}^{2} - 25](https://tex.z-dn.net/?f=y%20%3D%20%20%7Bx%7D%5E%7B2%7D%20%20-%2025)
We then get
![\frac{ {x}^{3} }{3} - 25x](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20%7Bx%7D%5E%7B3%7D%20%7D%7B3%7D%20%20-%2025x)
Evaluate at -3
![\frac{ - 3 {}^{3} }{3} - 25( - 3)](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20-%203%20%7B%7D%5E%7B3%7D%20%7D%7B3%7D%20%20-%2025%28%20-%203%29)
![- 27 + 75 = 48](https://tex.z-dn.net/?f=%20-%2027%20%2B%2075%20%3D%2048)
Then we evaluate at 0
![\frac{0 {}^{3} }{3} - 25(0) = 0](https://tex.z-dn.net/?f=%20%5Cfrac%7B0%20%7B%7D%5E%7B3%7D%20%7D%7B3%7D%20%20-%2025%280%29%20%3D%200)
Next, we subtract the the answer then we get
![48 - 0 = 48](https://tex.z-dn.net/?f=48%20-%200%20%3D%2048)
Answer: Choice B
Range = {-3, 1, 5}
============================================
Explanation:
The domain is the set of all possible input x values. The range is the set of all possible y outputs.
Plug in each x value from the domain, one at a time, to get its corresponding range y value.
--------------------
Start with x = -3
f(x) = 2x+3
f(-3) = 2(-3)+3
f(-3) = -6+3
f(-3) = -3
So -3 is in the range.
--------------------
Move onto x = -1
f(x) = 2x+3
f(-1) = 2(-1)+3
f(-1) = -2+3
f(-1) = 1
1 is also in the range
--------------------
Finally plug in x = 1
f(x) = 2x+3
f(1) = 2(1)+3
f(1) = 2+3
f(1) = 5
The value 5 is the final value in the range.
--------------------
All of those values form the set {-3, 1, 5} which is the complete range.